In vivo Photonic Stimulation of Sciatic Nerve with a 1470 nm Laser - Marie Dautrebande; Pascal Doguet; Simon-Pierre Gorza; Jean Delbeke; Yohan Botquin; Antoine Nonclercq (PAGEPress Publications, 2016)
Photonic stimulation is a new modality of nerve stimulation, which could overcome some of the electrical stimulation limitations. In this paper, we present the results of photonic stimulation of rodent sciatic nerve with a 1470 nm laser. Muscle activation was observed with radiant exposure of 0.084 J/cm2.